Unjuk Rasa Anarkis: Analisis Faktor dan Peran Kepolisian dalam Penanggulangan - Dedy Indriyanto (Universitas Bhayangkara Jakarta Raya, 2023)
This article aims to explain the factors that influence the occurrence of anarchist demonstrations and the role of the Indonesian National Police (Polri) in dealing with anarchist demonstrations. The author uses an approach using normative juridical methods supported by interviews. The primary legal data sources used are Law No. 9 of 1998 and the National Police Chief's Regulations relating to the handling of anarchist demonstrations. The results of the research show that peaceful demonstrations became anarchic due to the presence of provocateurs from groups outside the demonstration masses. Apart from that, this research also found that more anarchist demonstrations were carried out by masses of student groups compared to other social groups, such as workers or political parties. This article concludes that anarchist demonstrations are not a single factor, non-processional police can also trigger anarchist demonstrations.